1989
DOI: 10.1111/j.1600-0722.1989.tb01608.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐year study of the efficacy of a dentifrice containing zinc citrate and triclosan to maintain gingival health

Abstract: – In a previous study we demonstrated that gingival health could be maintained in a group of highly motivated nurses using a dentifrice containing a zinc salt and triclosan. We have now investigated the effect of the experimental dentifrice on a group of less motivated men. One hundred and three male students were given oral hygiene instruction (OHI) and their teeth were professionally cleaned. For each individual, both the instruction and cleaning were completed in a single 15‐min period. Two balanced groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The study design was similar to that described previously (3). The study design was similar to that described previously (3).…”
Section: Methodsmentioning
confidence: 99%
“…The study design was similar to that described previously (3). The study design was similar to that described previously (3).…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of triclosan formulations has been improved by either adding a copolymer to enhance its retention in the mouth or by adding zinc citrate to provide additional antibacterial activity. These formulations have been shown in randomised controlled trials (Type 2) to provide significant reductions in plaque and significant improvements in gingival health 58,59 when compared with a fluoride toothpaste alone. In studies of 3 years duration the triclosan/copolymer formulation was reported to reduce the onset of periodontitis in adolescents 60 and the further progression of periodontitis in at-risk adults.…”
Section: Toothpastementioning
confidence: 99%
“…Systematic reviews of six-month clinical studies have concluded that formulations containing triclosan and copolymer significantly improve plaque control and periodontal health (15)(16)(17). Toothpastes containing triclosan and zinc citrate are also effective in improving plaque control and gingival health (18)(19)(20)(21).…”
Section: E978mentioning
confidence: 99%